Takotsubo cardiomyopathy Afatinib-related in a non-small cell lung cancer patient: Case report - Ramos, German E.; Caglevic, Christian; Bulnes, Juan F.; Panay, Sergio E.; Zapata, Mario I.; Daniele, Andrés J.; Rodríguez, Manuel E. (Frontiers in Cardiovascular Medicine, 2022)
Endothelial Growth Factor Receptor (EGFR) mutations are frequently found among NSCLC patients. Second-generation Tyrosine Kinase Inhibitor (TKI) Afatinib is frequently used in this population of patients achieving better results than cytotoxic chemotherapy in terms of survival and progression. Afatinib-related cardiotoxicity has been rarely reported. Here we comment on a clinical case of a Takotsubo Cardiomyopathy Afatinib-induced in an NSCLC patient.